Knowledge, Attitude, and Readiness to Practice (KArP) of Healthcare Professionals toward disaster management at Ali-Abad teaching hospital (one of the major public hospitals in Afghanistan).: Knowledge, Attitude, and Readiness to Practice (KArP) of Healthcare Professionals toward disaster management (Turkey Health Literacy Journal, 2023)
Objective: This study aimed to evaluate the knowledge, attitude, and Readiness to Practice (KArP) level of healthcare staff at Ali Abad teaching hospital in Kabul Afghanistan toward disaster management and preparedness. Methods: A cross-sectional study was conducted using a self-administered questionnaire in March 2023 with some 107 healthcare staff at Ali-Abad teaching hospital. The chi-square test was used to compare the difference in KArP status between the independent categorical variables. Mann-Whitney U and Kruskal-Wallis tests were used to compare the participants’ scale scores across their socio-demographic characteristics. Results: Ninety-eight (91.58%) healthcare staff accepted to participate in the study. Only 35.7% of health workers had a good level of knowledge about disaster management and preparedness, 53.1% of healthcare personnel had a positive attitude toward disaster management and preparedness, and nearly 54.1% of health workers scored moderate on the Readiness to Practice scale. Medical doctors, healthcare staff with longer work experience, and those with a history of exposure to disasters had significantly higher KArP scores than their comparative groups. Conclusion: A moderate level of attitude among respondents is a good opportunity to adopt our educational policies to increase the level of knowledge and Readiness to Practice among health workers in Afghanistan.